Newborn care knowledge and practices among mothers in Baguio City, Philippines: A descriptive correlational study - Frildah Aifondoka Vongula; Rachelle Gay Rosario Pacial (Journal of Healthcare Administration)
Background: Maternal knowledge and practices on newborn care are crucial in ensuring the well-being of infants, particularly in areas such as cord care, pain and fever management, and stimulation of senses. The Department of Health (DOH) and other health programs aim to promote better newborn care practices, but maternal knowledge gaps may persist.